Role of topical use of natural honey in chronic non healing ulcer: a prospective non randomized comparative trial on 150 patients - Kochar, Mahinder Pal (International Surgery Journal, 2020)
Background: Natural honey procured from any source on topical application on chronic non-healing ulcer has unique property to reduce pain, inflammation, oedema, deodorization, rapid disinfection, stimulate desloughing, promote neo vascularization, granulation, collagen synthesis, epithelialization and thus boost the process of ulcer healing. Methods: In this study a prospective, non-randomized trial was done on 150 patients divided in two groups of 75 each (group-A with honey dressing and group-B without honey dressing), of different age and sex having chronic non healing ulcers situated on various parts of the body. Natural honey available from various sources was used. Results: Most of the patients fall in their most productive and active 3rd and 4th decade of life. Pain and fever were the main reason of restricted mobility and absence from work reflecting productivity. Bacterial contamination, presence of necrotic tissue, bed ridden condition, old age, debility, DM, ulcer present in the vicinity of joint were found major cause of delay in the process of healing. The cost effectiveness, easy availability, ease of application makes natural honey a better alternative in the management of chronic non healing ulcer. Conclusions: Cost effectiveness, easy availability, ease of application, increasing healing process makes natural honey a better alternative in the management of chronic non healing ulcer and safe to use in diabetic patients as well.